Ótica e a visão humana - Bueno, André Buzatto Correa [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Optics consists in the study of interaction of light with physical systems. The human vision is a product of the interaction of light with the eye (a very peculiar physical system). Here we present a basic study of the relationship between the optics and human vision, including: - The fundaments and physicals properties who characterize the light and the colors and the characteristics of the incidence mediums. - The basics laws of geometrical optics, based in the rectilinear propagation of light in the form of a light ray, in the independence of light rays and in the principle of reversibility of the light beams. This principle is present in the process of image formations in lenses and mirrors and applied in the study of image formation in the human eye. - The refraction and reflection laws and types of lenses, who permits the construction of optics devices for the study of physical universe, and the appliances to correct vision diseases. - Presents the human vision process as consisting in the reception of light (electromagnetic radiation in the zone of wavelength visible to us) through the eye and the sending of information obtained by the retina to the brain where it is interpreted. The vision involves a biophysical relation between the light and the biological structure of the eye who is constituted by cornea, iris, crystalline and retina. Analyzes is made of how some parts of the eye performs a function in the reception and sending of information of the images to the brain

A óptica consiste no estudo da interação da luz com sistemas físicos, e a visão humana é fruto da interação da luz com o globo ocular (um sistema físico muito particular). Realiza-se nesse trabalho um estudo básico da relação entre a óptica e a visão humana e apresenta-se: - Os fundamentos e as propriedades físicas que caracterizam a luz e as cores e características dos meios de incidência - As leis básicas da óptica geométrica, baseadas na propagação retilínea da luz na forma de raio de luz, na independência dos raios de luz e no principio de reversibilidade dos feixes de luz. Esses princípios são apresentados no processo de formação das imagens em lentes e espelhos e aplicados ao estudo da formação da imagem no olho humano. - As leis da refração e reflexão e tipos de lentes, que permitem a construção de dispositivos ópticos para o estudo do universo físico e dos aparelhos de correção de defeitos da visão. - Analisa-se o processo de visão humana que consiste na recepção da luz (radiação eletromagnética na faixa de comprimento de onda visível para nós) pelo olho e o envio da informação obtida pela retina para a interpretação pelo cérebro. A visão envolve a relação biofísica entre a luz e a estrutura biológica do olho constituída pela córnea, a íris, o cristalino e a retina. Avalia-se como cada parte do olho executa uma função na recepção e envio da informação das imagens até o cérebro
Keywords: Otica; Visão; Distúrbios da visão; Luz; Refração; Reflexão (Otica); Olhos; Ondas eletromagneticas; Otica fisiologica